2022
DOI: 10.2991/absr.k.220309.048
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Forage Species in Oil Palm Plantation Area in Kolaka Regency

Abstract: The diversity of greenery species in oil palm plantations is a source of animal feed. The research aims to identify the type of forage as a source of animal feed in the area of oil palm plantations in Watubangga Subdistrict Kolaka Regency, conducted in April to June 2021 using survey methods and direct observations on oil palm plantation areas. Observation and measurement of forage type used quadrant 1 m x 1 m in the area of oil palm plantations aged 7 years. The results of forage identification were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…These problems can be overcome by implementing intensive and extensive livestock-rearing systems that combine crops with livestock on plantations [31], [32]. In general, so that the community is not disturbed by the livestock rearing system (X2.4), an intensive system is a solution so as not to interfere with the activities of road users (66%).…”
Section: X2mentioning
confidence: 99%
“…These problems can be overcome by implementing intensive and extensive livestock-rearing systems that combine crops with livestock on plantations [31], [32]. In general, so that the community is not disturbed by the livestock rearing system (X2.4), an intensive system is a solution so as not to interfere with the activities of road users (66%).…”
Section: X2mentioning
confidence: 99%
“…This fact is relevant to the opinion of Permatasari et al (2024) that increasing ambient temperatures due to climate change have significantly impacted human physical and mental health and safety. For example, when the sun shines fully, the air conditions under shady trees cannot penetrate the canopy, so the canopy feels more shady, cool, humid, and comfortable (Sandiah et al 2022;Wati and Fatkhuroyan 2017). Vegetation in the form of trees functions as climate control for environmental comfort because the tree canopy absorbs heat from the sun's rays so that it lowers air temperature, increases RH, and the overall microclimate is cool (Findlater et al 2022;Kandari et al 2021).…”
Section: Further Test Of Least Significant Difference (Lsd)mentioning
confidence: 99%
“…This carrying capacity is lower than as reported by Daru et al (2014) which can accommodate 1.44 AU ha -1 year -1 at a 3-year-old plantation and 0.71 AU ha -1 year -1 at a 7-year-old plantation. Another study reported that 7-year-old oil palm plantations could accommodate 1.35 AU ha -1 year -1 (Sandiah et al 2022) and without herbicide spraying treatment, 10-year-palm oil plantations could accommodate 0.51 AU ha -1 year -1 , while oil palm plantations treated by herbicide spraying can accommodate 0.42 AU ha -1 year -1 (Endrawati et al 2019). Not all oil palm plantations have forage plants consumable by livestock.…”
Section: Carrying Capacitymentioning
confidence: 99%